Studi Kasus Motion Comic Patriot Praha sebagai Media Hiburan - Mugia, Sultan Tanu; Susanti, Elizabeth (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2024)
Motion comics combine static images with visual effects that produce the illusion of moving images. This media is rarely used in Indonesia, but its success in other countries can be proof that motion comics have potential in the Indonesian market. This case study aims to research and analyze how a motion comic is formulated and presented. The research method will use a qualitative method by conducting in-depth observations of motion comics through literature reviews as references and analyzing the Patriot Prahara motion comic. This case study will produce a guide on creating motion comic content that is interesting for young people or Generation Z as a means of entertainment